Biomarkers in the Early Detection and Diagnosis of Alzheimer’s Disease - Rucka, Aleksandra; Kowalski, Mateusz; Rucki, Michał; Cieleban, Nikodem; Gajewska, Maja; Modliborska, Magdalena (Journal of Education, Health and Sport, 2026)
Background. Alzheimer’s disease (AD) accounts for 60–70% of the over 57 million dementia cases worldwide and is projected to nearly triple by 2050. Neuropathology precedes symptoms by roughly two decades, and the approval of anti-amyloid therapies has made biomarker-confirmed early diagnosis a clinical priority. Aim. This narrative review synthesizes evidence on cerebrospinal fluid (CSF), blood, neuroimaging, genetic, retinal, and emerging molecular biomarkers for early detection of AD, framed within the 2024 revised NIA-AA biological criteria. Material and methods. PubMed, MEDLINE, Google Scholar, the Journal of Education, Health and Sport, and Quality in Sport were searched for studies and consensus documents published between 2014 and 2026. Six mandatory references were integrated with seventeen additional peer-reviewed sources. Results. CSF Aβ42/40, total tau, and p-tau181 remain reference-standard markers. Plasma p-tau217 has emerged as the leading minimally invasive biomarker, with areas under the curve of 0.92–0.96 against amyloid PET. Serum neurofilament light and glial fibrillary acidic protein support staging and differential diagnosis. Amyloid and tau PET enable in vivo Braak staging; structural MRI tracks hippocampal atrophy. APOE ε4 genotyping has regained clinical relevance in the anti-amyloid era. Optical coherence tomography, metabolomics, microRNAs, and AI-driven multimodal models expand the diagnostic frontier. Conclusions. AD can now be detected biologically before symptoms become disabling. Translating plasma assays and AI-supported imaging into routine practice is the central challenge of the coming decade.